2014
DOI: 10.1097/qad.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of virologic response in persons who start antiretroviral therapy during recent HIV infection

Abstract: Objective Despite evidence supporting antiretroviral therapy (ART) in recent HIV infection, little is known about factors that are associated with successful ART. We assessed demographic, virologic, and immunologic parameters to identify predictors of virologic response. Design A 24-week observational study of ART on persons enrolled within 6 months of their estimated date of infection (EDI) evaluated baseline demographics and the collection of blood and gut specimens. Methods Flow cytometry analyses of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…This dichotomy suggests that the previously observed increases occurred within lymphoid tissue structures (e.g., lymphoid aggregates) and not within the effector sites of the gut. This is in concordance with several previous studies demonstrating that CD4 + T cells in the GI tract remained significantly lower than in HIV − controls, despite effective prolonged cART (14, 3943). It is encouraging to note that several individuals treated during FI/II approached HIV − baseline CD4 + T cell levels in the LP and demonstrated significant increases in CD4 + T cells from the 24 to 96 week time point.…”
Section: Discussionsupporting
confidence: 93%
“…This dichotomy suggests that the previously observed increases occurred within lymphoid tissue structures (e.g., lymphoid aggregates) and not within the effector sites of the gut. This is in concordance with several previous studies demonstrating that CD4 + T cells in the GI tract remained significantly lower than in HIV − controls, despite effective prolonged cART (14, 3943). It is encouraging to note that several individuals treated during FI/II approached HIV − baseline CD4 + T cell levels in the LP and demonstrated significant increases in CD4 + T cells from the 24 to 96 week time point.…”
Section: Discussionsupporting
confidence: 93%
“…The enteropathy associated with HIV infection is characterized by microbial over-growth in the intestinal lumen and disrupted intestinal permeability resulting in increased levels of lipopolysaccharides (LPS) and 16S rRNA in blood plasma. Such microbial translocation most likely leads to local and systemic immune activation, characterized by increased levels of pro-inflammatory cytokines such as tumour-necrosis-factor α (TNF-α), neopterin, cluster of differentiation 14 (CD14), interleukin-8 (IL-8), and interleukin-6 (IL-6) [6], [7], [8], [9]. In particular, plasma neopterin is an established marker of monocyte activation and was repeatedly associated with HIV disease progression, greater peripheral monocyte HIV DNA reservoirs and negative neurocognitive and cardiovascular outcomes [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hartigan-O’Connor et al previously reported that IRU is most likely to develop in patients with the greatest degree of immune dysfunction prior to HAART [22]. Additionally, older age groups have been correlated with quicker seroconversion to AIDS in the pre-HAART era, as well as higher rates of immunologic failure and persistent HIV viraemia in the HAART era [23]. Thus, it is plausible that younger HIV patients have a more intact immune system that may not have such heightened sensitivity to CD4 T cell responses, consequently delaying their development of IRU until the occurrence of further immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%